2015
DOI: 10.1093/bioinformatics/btv281
|View full text |Cite
|
Sign up to set email alerts
|

HTT-DB: Horizontally transferred transposable elements database

Abstract: bdotto82@gmail.com or gabriel.wallau@gmail.com.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 12 publications
1
54
0
Order By: Relevance
“…2 and Dataset S2). This unprecedented figure is more than four times higher than the total number of HTT events reported so far in metazoans, plants, and fungi combined (10). Such a high number is still not unexpected, given that studies focusing on one or a few TEs often found one or more HTT events between multiple, distantly related taxa (11,(14)(15)(16)22).…”
Section: Significancementioning
confidence: 76%
See 1 more Smart Citation
“…2 and Dataset S2). This unprecedented figure is more than four times higher than the total number of HTT events reported so far in metazoans, plants, and fungi combined (10). Such a high number is still not unexpected, given that studies focusing on one or a few TEs often found one or more HTT events between multiple, distantly related taxa (11,(14)(15)(16)22).…”
Section: Significancementioning
confidence: 76%
“…In fact, most of the genetic material that is horizontally transferred in animals and plants consists of transposable elements (TEs) (9)(10)(11), which are pieces of DNA able to move from a chromosomal locus to another (12). The greater ability of TEs to move between organisms certainly relates to their intrinsic ability to transpose within genomes, which genes cannot do.…”
mentioning
confidence: 99%
“…The presence of such patterns can be explained by an exchange of TEs by these species or independent acquisitions from a third source, which characterizes a phenomenon known as HTT. HTT events have been reported throughout the eukaryote tree of life in recent years, and several of these events were reported for vertebrate species [13]. For instance, the SPIN transposon was found in more than 17 distantly related tetrapod species, including mammals as well as an African frog and a lizard, showing high similarity and patchy distribution [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…However, compelling evidence in a wide variety of taxa has increasingly revealed that Horizontal Transfer (HT), the exchange of genetic material between isolated sexual species, is an effective way in which TEs invade new genomes and colonize other species [11,12]. Currently, around 2853 Horizontal Transposon Transfer (HTT) events have been reported [13]. The mariner family of Class II DNA transposons has the highest number of HTT cases reported (52) [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation